2016
DOI: 10.1144/petgeo2015-084
|View full text |Cite
|
Sign up to set email alerts
|

Geodynamical framework and hydrocarbon plays of a salt giant: the NW Mediterranean Basin

Abstract: The North Western Mediterranean Basin developed during the Oligocene-Miocene rifting of the Eastern Iberian-European magma-poor continental margin. The margin developed as a result of back-arc extension associated with the roll-back of the retreating Calabrian-Tethys subduction zone. Reinterpretation of 2D regional seismic reflection data suggests that rifting took place by hyperextension of the Iberian-European lithosphere. This process led to the seaward arrangement of distinct crustal domains, namely proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 66 publications
4
25
0
Order By: Relevance
“…A population of minibasins have subsided or are actively subsiding into, and have translated downslope above, the extremely rugose base of the salt canopy. This structural setting differs from the salt‐detached slopes described in prior related studies in three key ways (e.g., Dooley et al, ; Dooley & Hudec, ; Ferrer et al, ; Gaullier et al, ; Granado et al, ; Loncke et al, ). First, rather than having a prekinematic supra‐canopy interval of fairly uniform thickness, the supra‐canopy is instead composed of minibasins of variable thickness.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…A population of minibasins have subsided or are actively subsiding into, and have translated downslope above, the extremely rugose base of the salt canopy. This structural setting differs from the salt‐detached slopes described in prior related studies in three key ways (e.g., Dooley et al, ; Dooley & Hudec, ; Ferrer et al, ; Gaullier et al, ; Granado et al, ; Loncke et al, ). First, rather than having a prekinematic supra‐canopy interval of fairly uniform thickness, the supra‐canopy is instead composed of minibasins of variable thickness.…”
Section: Introductionmentioning
confidence: 61%
“…Salt‐detached gravity gliding/spreading systems with a relatively smooth base‐of‐salt have commonly been interpreted in terms of kinematically linked domains of upslope extension and downslope shortening, which may be connected by a domain of midslope translation (Figure a) (e.g., Brun & Fort, , ; Cobbold & Szatmari, ; Jackson, Jackson, & Hudec, ; Granado et al, ; Hudec & Jackson, ; Peel, ; Rowan, Peel, & Vendeville, ). However, recent work has shown that strain patterns are more complex where translation occurs above base‐of‐salt relief; for at least two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the Western Mediterranean basin is a younger though complex system of back-arc basins related to the north-western Tethyan subduction, initiated by continental rifting in the Oligocene with the opening of the Valencia Trough (e.g. Granado et al, 2016). It continued with oceanic spreading in the Algero-Balearic Basin and opening of the Provençal Basin by counterclockwise rotation of the Corsica-Sardinia block.…”
Section: Geological Settingmentioning
confidence: 99%
“…1). The fields are located in the Valencia Trough, a sub-basin that is part of the northwestern Neogene Mediterranean rift system (Roca, 1994;Maillard and Mauffret, 1999;Roca et al, 1999;Granado et al, 2016;Klimowitz et al, 2018;Roma et al, 2018). The Valencia Trough developed under an extensional tectonic regime from the Oligocene to recent times (Roca et al, 1999) and is characterized by northeast-southwest-oriented horsts and grabens.…”
Section: Geological Settingmentioning
confidence: 99%